Verbal Sign on Coldplay’s Song “Biutyful” (Semiotic Analysis) - Ni Ketut Novia Anggreni; Ida Ayu Mela Tustiawati (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
The purpose of this study is to analyze and interpret the meanings or messages conveyed by the semiotic indicators present in three specific scenes from Coldplay's